SOSIALISASI CABANG OLAHRAGA CRICKET PADA GURU SMP SE-KABUPATEN SRAGEN TAHUN 2020 - Ratna Kumala Setyaningrum; Herywansyah; Slamet Sudarsono (FKIP UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2021)
Abstract Cricket is a team game sport that is competed in regional and national sporting events. The philosophical meaning contained in Cricket is in the form of exemplary attitudes, enthusiasm and harmony between healthy competition and cohesiveness in teamwork. Cricket sports teaches about controlling emotions, maintaining patience, forming confidence in self-potential or team strength. Sragen Regency is one of the areas that still lacks knowledge about the sport of cricket, so it is necessary to deliver material in the form of socialization of cricket sports. Through this service activity, socialization was carried out to junior high school teachers in Sragen Regency which was held on December 5, 2020 at GOR DIPONEGORO, Sragen Regency. The purpose of the implementation of this socialization is to try to foster exemplary attitudes in the sport of Cricket, to provide knowledge about the sport of Cricket in the form of basic technical knowledge, facilities and infrastructure as well as the rules of the Cricket sport competition. Keywords: socialization, cricket, exemplary